Implementasi Moderasi Beragama pada Ekstrakulikuler Rohani Islam di Satuan Pendidikan - Anwar, Rosyida Nurul; Winanda, Intan; Febrianti, Candra Surya; Saputri, Dita Nur; Mustofiah, Diva Nur (Ideas Publishing, 2024)
Indonesia is a country that is rich in ethnic, cultural, tribal, racial and religious diversity. Diversity must be maintained to create harmony in every society, including Islamic Spiritual extracurricular students. A moderate attitude is part of efforts to maintain harmony in religion. This research aims to determine how religious moderation is implemented among Rohani Islam extracurricular members. This research uses a descriptive qualitative approach. Data collection techniques are observation, interviews and documentation. The subjects of this research were 14 Rohani Islam members at SMA Negeri 1 Barat, Magetan Regency. This research showed that members of Rohani Islam already understand the concept of religious moderation and can implement an attitude of religious moderation in the school environment by respecting religious differences and ways of worship and inviting friends to have a moderate attitude. Religious moderation in extracurricular activities at school can be part of maintaining harmony between individuals